(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The retailing as aprocess is least understood in India. For a start-up, it is important to have acomprehensive view of what retailing means and where he wants to focus on. Mostof the world player like Wal Mart-Mart, Circuit city, Sears have developed inhouse expertise in each of these processes like The Retail design group,various trading houses etc. many have out-sourced these due to lack ofexpertise. The Indian organized sector needs to understand how to manage eachof these processes and success will be contingent upon mastering them.